Biochemical and Molecular Characterization of a Flavonoid 3-O-glycosyltransferase Responsible for Anthocyanins and Flavonols Biosynthesis in Freesia hybrida - Sun, Wei; Liang, Lingjie; Meng, Xiangyu; Li, Yueqing; Gao, Fengzhan; Liu, Xingxue; Wang, Shucai; Gao, Xiang; Wang, Li (Frontiers in Plant Science, 2016)
The glycosylation of flavonoids increases their solubility and stability in plants. Flowers accumulate anthocyanidin and flavonol glycosides which are synthesized by UDP-sugar flavonoid glycosyltransferases (UFGTs). In our previous study, a cDNA clone (Fh3GT1) encoding UFGT was isolated from Freesia hybrida, which was preliminarily proved to be invovled in cyanidin 3-O-glucoside biosynthesis. Here, a variety of anthocyanin and flavonol glycosides were detected in flowers and other tissues of F. hybrida, implying the versatile roles of Fh3GT1 in flavonoids biosynthesis. To further unravel its multi-functional roles, integrative analysis between gene expression and metabolites was investigated. The results showed expression of Fh3GT1 was positively related to the accumulation of anthocyanins and flavonol glycosides, suggesting its potential roles in the biosynthesis of both flavonoid glycosides. Subsequently, biochemical analysis results revealed that a broad range of flavonoid substrates including flavonoid not naturally occurred in F. hybrida could be recognized by the recombinant Fh3GT1. Both UDP-glucose and UDP-galactose could be used as sugar donors by recombinant Fh3GT1, although UDP-galactose was transferred with relatively low activity. Furthermore, regiospecificity analysis demonstrated that Fh3GT1 was able to glycosylate delphinidin at the 3-, 4'- and 7- positions in a sugar-dependent manner. And the introduction of Fh3GT1 into Arabidopsis UGT78D2 mutant successfully restored the anthocyanins and flavonols phenotypes caused by lost-of-function of the 3GT, indicating that Fh3GT1 functions as a flavonoid 3-O-glucosyltransferase in vivo. In summary, these results demonstrate that Fh3GT1 is a flavonoid 3-O-glycosyltransferase using UDP-glucose as the preferred sugar donor and may involve in flavonoid glycosylation in F. hybrida.